Civil Society and Global Finance - Schnabel, Albrecht (Civil Society and Global Finance, 2002)
This key text brings together twenty activists, officials and researchers from the five continents to discuss this burning question of today's globalization debate. Providing rare, authoritative analyses by those who deal with the issues first hand, Civil Society and Global Finance is rich in insight and policy ideas for decision-makers, students and concerned citizens.